2001
DOI: 10.1007/s00268-001-0151-z
|View full text |Cite
|
Sign up to set email alerts
|

Grade IV Renal Injuries: Evaluation, Treatment, and Outcome

Abstract: Of our last 2483 renal trauma patients, 113 had grade IV injuries. In most the mechanism was a penetrating injury (60%: 30% gunshot, 30% stab wounds). Associated injuries were common (80%) and hospital stays prolonged, averaging 16 days. Most of the patients (70%) required transfusion, some massively (average volume 4.4 liters, range 0-30 liters). Surprisingly, not all patients with grade IV renal injuries had gross hematuria: 25% had microhematuria, and 4% had neither microscopic nor gross hematuria. Computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 32 publications
2
61
0
6
Order By: Relevance
“…In our study, no surgical procedure was performed for the patients with grade 1-2-3 renal traumas, and all of these patients had a successful recovery through conservative treatment. Conservative treatment is contraindicated in cases where there is a hemodynamic instability due to bleeding and a developing pulsatile retroperitoneal hematoma as well as ongoing hypotension despite the transfusion and suspicion of the renal pelvis and ureteral injury [17,18]. In a study by Santucci et al (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, no surgical procedure was performed for the patients with grade 1-2-3 renal traumas, and all of these patients had a successful recovery through conservative treatment. Conservative treatment is contraindicated in cases where there is a hemodynamic instability due to bleeding and a developing pulsatile retroperitoneal hematoma as well as ongoing hypotension despite the transfusion and suspicion of the renal pelvis and ureteral injury [17,18]. In a study by Santucci et al (17).…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment is contraindicated in cases where there is a hemodynamic instability due to bleeding and a developing pulsatile retroperitoneal hematoma as well as ongoing hypotension despite the transfusion and suspicion of the renal pelvis and ureteral injury [17,18]. In a study by Santucci et al (17). 78% of patients with grade 4 trauma were received renal exploration, and renography and nephrectomy were performed for 69% and 9% of them.…”
Section: Discussionmentioning
confidence: 99%
“…Medical management depends on the grades of renal trauma. Recent studies showed that majority of low grade of renal trauma can be conservatively treated while high grade injure often needs surgery [17]. Up to 88% of patients with grade III and 78% of grade IV had conservative treatment; while 91% of grade V injuries needed the surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…Yatak istirahatı ile destekleyici bakım ve gözlem stabil hastalar için yeğlenen tedavi yöntemidir ve morbiditede herhangi bir artış olmaksızın daha düşük bir nefrektomi oranı ile ilişkilidir. 4. ve 5. derece yaralanmalarda hasta yüksek ekplorasyon, nefrektomi ve komplikasyon oranlarına sahip olmakla birlikte, stabil hastalarda başlangıçta konservatif bir yaklaşım uygulanabilir (23) . Soliter yaralanmalarda idrarla ekstravazasyon tanısı alan hastalar, %90'ın üzerinde bir oran ile büyük bir müdahale olmadan tedavi edilebilir (24) .…”
Section: Tedaviunclassified